PEMENUHAN KESEJAHTERAAN DAN KESEHATAN MENTAL ANAK ATAS PERCERAIAN ORANG TUA DI KECAMATAN TAMBUN SELATAN KABUPATEN BEKASI: Fulfillment of Children's Welfare and Mental Health Upon Divorce of Parents in South Tambun Subdistrict, Bekasi Regency - Riska Saskia; Trubus Rahardiansah (AMICUS CURIAE, 2025)
The fulfillment of children’s welfare rights and mental health after parental divorce is a crucial aspect regulated under Law Number 4 of 1979 on Child Welfare. This study aims to examine the implementation of these rights and explore efforts that can be taken when children’s rights are not fully met. The main problems identified include the extent to which child welfare rights are implemented in accordance with the law, the factors that hinder their fulfillment within families and social environments, and the impact of unfulfilled rights on children’s psychological, social, and developmental conditions. The research employs a socio-legal descriptive method, using both primary and secondary data analyzed qualitatively. Findings show that the fulfillment of children’s rights after divorce has not been fully realized, particularly in spiritual, physical, and social aspects. Parents in Tambun Selatan Subdistrict face challenges due to negligence, economic limitations, low education levels, and lack of awareness. These shortcomings negatively affect children’s psychology, leading to inner conflict, declining academic performance, laziness, deviant behavior, adaptation difficulties, and reduced self-confidence. The study recommends active and comprehensive measures by both parents and government institutions to ensure the fulfillment of children’s welfare and mental health rights after divorce, in line with prevailing legal principles in Indonesia.